Factors associated with choice of attendant at birth and place of delivery: A re-analysis of the 1998 national demographic and health survey - Tan, Charity L. (Animo Repository, 2000)
Skilled attendance at birth is the single most effective measure to drastically reduce maternal mortality. Place of delivery is critical whenever an obstetric emergency that requires higher level of care occurs. This study sought to identify the factors that are associated with the choice of birth attendant and place of delivery. Data from the 1998 National Demographic and Health Survey was utilized for the study. Cross-tabulation and logistics regression were the statistical tools. Dependent variables were place of delivery, birth assistant, complications and pregnancy outcome. The study found that there is gross inequity in the maternal care system in the country. Births to richer, more educated urban resident mothers were more likely to have medical attendance and a health facility delivery. Also, the premise that high risk women would opt for higher level of care was not carried by the data. Women who were considered low risk had more positive pregnancy behavior than high risk women. Complications during delivery is a random event. No pattern can be discerned as to when or where complications will occur. In fact, higher percentage of health facility deliveries registered complications than those delivered at home. No pattern could also be made out for pregnancy outcome. One possible explanation was the number of cases of unsuccessful birth outcomes being too small to generate stable estimates. Organizational variables showed a weak relationship with choice of attendant at birth and place of delivery. Enabling environments for health financing and service delivery have to be enhanced if poor and marginalized women are to have access to skilled attendance at birth and health facility delivery. Also, the proportion of midwife-assisted delivery should be increased. Awareness of maternal health has to be enhanced.